1994
DOI: 10.1016/0014-5793(94)01136-2
|View full text |Cite
|
Sign up to set email alerts
|

Specific amino acid substitutions in human collagenase cause decreased autoproteolysis and reveal a requirement for a second zinc atom for catalytic activity

Abstract: We have previously reported the crystal structure of truncated human collagenase (domain II) complexed with a low molecular weight inhibitor. Attempts to crystallise full-length active collagenase (i.e. domain II + III) have been hindered by autoproteolysis at the domain II/III junction at high protein concentrations. To overcome this problem, we have generated an inactive enzyme via a H149-1 L,D151 +N double substitution which displaces the non-catalytic zinc atom, and shown that the altered collagenase is un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Similar mutagenesis in fibroblast collagenase has been demonstrated recently and the conversion of He 251 -> Ser and/or He 241 -> Leu leads to resistance to autoproteolysis when the active enzymes were stored at 4°C [30,31]-In contrast, mutagenesis of the Pi position of the peptide bonds cleaved by autoproteolysis has no effect on stability (mutant V), or leads to increased autoproteolysis (mutant IV).…”
Section: Effect Of the Hinge Mutations On Stability Of Active Neutropsupporting
confidence: 64%
“…Similar mutagenesis in fibroblast collagenase has been demonstrated recently and the conversion of He 251 -> Ser and/or He 241 -> Leu leads to resistance to autoproteolysis when the active enzymes were stored at 4°C [30,31]-In contrast, mutagenesis of the Pi position of the peptide bonds cleaved by autoproteolysis has no effect on stability (mutant V), or leads to increased autoproteolysis (mutant IV).…”
Section: Effect Of the Hinge Mutations On Stability Of Active Neutropsupporting
confidence: 64%
“…In addition, Kly18 possesses most of the structural details characteristic of MMP CDs that distinguish them from other metzincins: (i) the residue downstream of the third zinc‐binding histidine is always a serine, and it hydrogen bonds the aspartate residue in helix αC that binds the N‐terminus in physiologically relevant ‘superactive’ MMP variants (Reinemer et al ., 1994; Tallant et al ., 2010b), (ii) after this conserved serine, the downstream chain trace, which leads to the Met‐turn and is characteristic for MMPs, and the latter turn itself, are perfectly superimposable, (iii) the Met‐turn is stabilized through hydrogen bonds of its main‐chain with a conserved aspartate residue immediately downstream of the aforementioned one within helix αC, (iv) the characteristic loop structures found in Kly18, the S‐loop, the bulge‐edge segment, the S 1 ′‐wall forming segment – which includes the sequence Pro175–Tyr–Tyr177 – and the specificity loop, are essential hallmarks of mammalian MMP CDs (Tallant et al ., 2010b), (v) the S 1 ′ pocket is hydrophobic and designed to accommodate bulky hydrophobic side‐chains, (vi) in addition, Kly18 accomplishes with the structural requirements of another characteristic feature of the active‐site cleft of MMPs, i.e. the selectivity for proline in position P 3 of a substrate, through an S 3 pocket framed by His117 and Phe119 of strand βIV and Tyr106 of the S‐loop, (vii) the first part of the S‐loop includes an essential structural zinc site (Williams and Murray, 1994) formed by residues contained in conserved sequence stretches equivalent to Pro107–His–Asp–Gly–(Xxx) 3 –Phe–Asp–Gly110 of Kly18 (Fig. 2C), and finally (viii) the sequences found in Kly18 within the upper‐rim strand βIV, Leu115–Ala–His–Ala–Phe–Xxx–Pro121, and within strand βV, His133–Phe–Asp135, are likewise conserved among MMPs.…”
Section: Resultsmentioning
confidence: 99%
“…There may be subtle structural differences between the truncated forms of the MMPs and the mature full-length enzymes in relation to the role of the second “structural” zinc(II) ion. To overcome problems of autoproteolysis when attempting to crystallize full-length active HFC (domains II and III), mutation of two amino acids which chelate the “structural” zinc(II) ion was found to result in a loss of catalytic activity . However, while analysis of the zinc contents of truncated forms of prostromelysin-1 and progelatinase-A indicates the presence of two zinc(II) ions, only one zinc(II) ion is detected in the corresponding full-length enzymes, and it has been suggested that the C-terminal domain performs the role proposed for the “structural” zinc(II) ion in maintaining the structure of the enzyme catalytic domain …”
Section: Mmp Structural Studiesmentioning
confidence: 99%
“…To overcome problems of autoproteolysis when attempting to crystallize full-length active HFC (domains II and III), mutation of two amino acids which chelate the "structural" zinc(II) ion was found to result in a loss of catalytic activity. 93 However, while analysis of the zinc contents of truncated forms of prostromelysin-1 and progelatinase-A indicates the presence of two zinc-(II) ions, only one zinc(II) ion is detected in the corresponding full-length enzymes, and it has been suggested that the C-terminal domain performs the role proposed for the "structural" zinc(II) ion in maintaining the structure of the enzyme catalytic domain. 94 However, a recent structure of full-length porcine synovial collagenase (MMP-1), which includes the haemopexin-like domain III, reveals the presence of both "catalytic" and "structural" zinc(II) ions in the crystalline form.…”
Section: Mmp Structural Studiesmentioning
confidence: 99%